Mycosynthesis of Silica Nanoparticles Using Aspergillus niger: Control of Alternaria solani Causing Early Blight Disease, Induction of Innate Immunity and Reducing of Oxidative Stress in Eggplant - Marzough A. Albalawi; Amer M. Abdelaziz; Mohamed S. Attia; Ebrahim Saied; Hussein H. Elganzory; Amr H. Hashem (MDPI AG, 2022)
The threats to the life and production of crops are exacerbated by climate change and the misuse of chemical pesticides. This study was designed to evaluate the effectiveness of biosynthesized silica nanoparticles (SiO2-NPs) as an alternative to pesticides against early blight disease of eggplant. Antifungal activity, disease index, photosynthetic pigments, osmolytes, oxidative stress, antioxidant enzymes activities were tested for potential tolerance of eggplant infected with Alternaria solani. Silica nanoparticles were successfully biosynthesized using Aspergillus niger through green and ecofriendly method. Results revealed that SiO2-NPs exhibited promising antifungal activity against A. solani where MIC was 62.5 µg/mL, and inhibition growth at concentration 1000 µg/mL recorded 87.8%. The disease Index (DI) as a result of infection with A. solani reached 82.5%, and as a result, a severe decrease in stem and root length and number of leaves occurred, which led to a sharp decrease in the photosynthetic pigments. However, contents of free proline, total phenol and antioxidant enzymes activity were increased in infected plants. On the other hand, the treatment with SiO2-NPs 100 ppm led to a great reduction in the disease Index (DI) by 25% and a high protection rate by 69.69%. A clear improvement in growth characteristics and a high content of chlorophyll and total carotenoids was also observed in the plants as a result of treatment with silica nanoparticles in (healthy and infected) plants. Interestingly, the noticeable rise in the content of infected and healthy plants of proline and phenols and an increase in the activity of super oxide dismutase (SOD) and polyphenol oxidase (PPO). It could be suggested that foliar application of SiO2-NPs especially 100 ppm could be commercially used as antifungal and strong inducer of plant physiological immunity against early blight disease.